Correlates of Non-suicidal Self-Injury in Adolescent Psychiatric Patients in China - Zhang, Ji-Jie; Liu, Yin-Du; Zhang, Hua; Huang, Zhuo-Hui; Wang, Fei; Yang, Jing-Jing; Wang, Shi-Bin; Jia, Fu-Jun; Hou, Cai-Lan (Frontiers in Psychiatry, 2022)
Background: Non-suicidal self-injury (NSSI) has attracted more and more attention from schools, mental health workers and even the whole society in China. The aim of this study was to explore influencing factors and clinical characteristics of NSSI in adolescent psychiatric patients in China, and provide valuable information for the intervention and treatment of NSSI. Methods: The sample included 157 adolescents, 114 were female (72.6%), aged 12-18 years (M=15.39, SD=1.81). Assessments were performed using Childhood Trauma Questionnaire-Short Form, the Revised Olweus Bully/Victim Questionnaire, the modified version of Adolescents Self-Harm Scale, Montgomery–Asberg Depression Rating Scale, Brief Psychiatric Rating Scale, the Young Mania Rating Scale and the Mini International Neuropsychiatric Interview. Clinical characteristics were collected from electronic medical record system. Results: Adolescent patients with NSSI experienced more adverse life events including peer bullying, childhood trauma and romantic relationship trouble. They had more times of hospitalization, higher dosage of psychotic medication, and more severe depressive symptoms. Conclusions: It is very necessary to evaluate negative life events, including childhood trauma, peer bullying etc. in adolescent patients with NSSI. It has important clinical implications for evaluating the risk factors of NSSI and giving effective intervention treatment. Timely and effective treatment of these patients' depressive symptoms will also contribute to the relief of NSSI.